Histologic healing following tooth extraction with socket grafting using demineralised freeze-dried bone allograft (DFDBA), compared to undisturbed normal healing in humans: a randomised controlled clinical trial - Marnewick, J.C. (Johan) (University of Pretoria, 2020)
Dissertation (MSc Dent)--University of Pretoria, 2020.